Empowering Lecturers with ICT Skills to Enhance their Teaching Profession at PGSD Program University Muhadi Setiabudi - Moh. Toharudin; Widiharto Purnomo; Dalimawaty Kadir; Teti Berliani; Manesa (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study aimed to empower lecturers in the PGSD program at University Muhadi Setiabudi with ICT skills to enhance their teaching profession. The focus was on integrating technology effectively into the teaching and learning process. The research addressed the limited ICT skills among lecturers and aimed to bridge the gap through targeted training and professional development initiatives. Through comprehensive data collection and analysis, the study identified lecturers' specific ICT training needs and evaluated existing training programs. The findings highlighted areas where lecturers needed more proficiency in ICT tools and identified challenges in utilizing technology in their teaching practices. Based on the results, recommendations were made for improving ICT training programs for lecturers. These recommendations included providing hands-on workshops, ongoing support and mentoring, access to relevant resources and tools, and collaboration among lecturers to share best practices. The study emphasized the significance of empowering lecturers with ICT skills in preparing future primary school teachers for the digital era. The research made notable contributions to the field by filling the gap in the existing literature and providing insights into the specific context of the PGSD program at the University of Muhadi Setiabudi. Keywords: Empowering Lectures, Empowering ICT Skill, Teaching Profession